Optimization of low-carbon land use in Chengdu based on multi-objective linear programming and the future land use simulation model - Wu, Ran; Lan, Haifeng; Cao, Yuxin; Li, Pingyi (Frontiers in Environmental Science, 2022)
Optimizing the structure of land use is essential to the low carbon sustainable development of a region. This paper takes Chengdu, a typical western China city, as the case study. Firstly, using carbon emission coefficients of land use to calculate the carbon emissions. Then, based on multi-objective linear programming (MOP), economic development priority scenario (S1), low carbon economic development scenario (S2), and strengthening low carbon economic scenario (S3) are proposed. Finally, the future land use simulation (FLUS) model is used to predict the spatial layout of land use under the three scenarios. The result shows that from 1990 to 2020, the carbon emissions increased by 7617.61 thousand tons, with an annual growth rate of 3.75%. The main difference among the three scenarios is the occupied degree of farmland caused by the expansion of construction land, and the potential carbon reduction is 969.72 tons (5.2%), 2414.31 tons (13.1%), and 3878.89 tons (21.0%) in S1, S2 and S3, respectively. The FLUS model shows that the conversion mainly occurs around the urban built-up area of Chengdu. This research can provide planning suggestions for the low-carbon development of Chengdu and a reference for other regions.